Feeling like the enemy: the emotion management and alienation of hospital doctors - Byrne, John-Paul; Creese, Jennifer; McMurray, Robert; Costello, Richard W.; Matthews, Anne; Humphries, Niamh (Frontiers in Sociology, 2023)
Globally, an epidemic of psychological distress, burnout, and workforce attrition signify an acute deterioration in hospital doctors’ relationship with their work – intensified by COVID-19. This deterioration is more complicated than individual responses to workplace stress, as it is heavily regulated by social, professional and organisational structures. Moving past burnout as a discrete ‘outcome’, we draw on theories of emotion management and alienation to analyse the strategies through which hospital doctors continue to provide care in the face of resource-constraints and psychological strain. We used Mobile Instant Messaging Ethnography (MIME), a novel form of remote ethnography comprising a long-term exchange of digital messages to elicit ‘live’ reflections on work-life experiences and feelings. The results delineate two primary emotion-management strategies – acquiescence and depersonalisation – used by the hospital doctors to suppress negative feelings and emotions (e.g. anger, frustration, guilt) stemming from the disconnect between professional norms of expertise and self-sacrifice, and organisational realities of impotence and self-preservation. Illustrating the continued relevant of alienation, extending its application to doctors who disconnect to survive, we show how the socio-cultural ideals of the medical profession (expertise, self-sacrifice) are experienced through the emotion-management and self-estrangement of hospital doctors. Practically, the deterioration of hospital doctors’ relationship with work is a threat to health systems and organisations. The paper highlights the importance of understanding the social structures and disconnects that shape this deteriorating relationship and the broad futility of self-care interventions embedded in work contexts of unrealised professional ideals, organisational resource deficits and unhappy doctors, patients and families.